Female Madness: love and cholera - Campista, Valesca (LINKSCIENCEPLACE, 2025)
This article focuses the woman’s stand in the psychoanalysis field. The starting point is a fictitious character called Joana that belongs to Chico Buarque and Paulo Pontes’work. In Brazilian literature Medeia is Joana, a woman that shows her sorrow by leaving alone by the man she loves, a madness of the woman.by experiencing the excess, the chaos without moderation from cholera to love,performing what Lacan calls in the 70s "gozo outro ". By means of psychoanalysis, we discuss Joana’s subjective posture and show how affected she is in a hysterical way in an unique way by the jouissance modality whose devastating affects led her to commit suicide.